PERBEDAAN KEMATANGAN SOSIAL DITINJAU DARI PENGALAMAN MENGIKUTI KELOMPOK BERMAIN - Nawang Warsi Wulandari (University of Merdeka Malang, 2013)
Not all students who get in formal education have a considerable social maturity. This poses a problem in the first years of formal education or primary school. Social maturity is one person's development as seen from the feeling of self-assessment as well as the ability to present themselves appropriately in groups or different social environments (Hasan, 1981). The subjects involved in this study there were 80 students, consisting of: 40 students who had followed the group playing experience and 40 students who do not have the experience to follow the playing group. Criteria for study subjects was following a group play experience for at least 1 year in a row or do not have the experience to follow the play at all. The method used to collect data is observation and documentation methods. This method is used to obtain data on the social maturity. Observation of the child's behavior is done by using the method of systematic observation. This observation is used in the rating scale. Rating scale is the recording of symptoms according to their levels. In this observation used 2 people rater, the researcher and the classroom teacher. documentation methods used to obtain data on the identity of the subject, age, birth order and whether the experience to follow the playing group. The data obtained in this study will be analyzed by using 3-Way Anova, in order to see the difference between the social maturity of the child who has the experience and the play follows a group of children who do not have the experience to follow the playing group, taking into account gender and birth order. The results of data analysis obtained with F = 0.441 p = 0.000. It shows there is differences social maturity between children who had followed the group experience playing with children who do not have the experience to follow the playing group. The mean social maturity children who do not have the experience to follow the play = 150.750. The mean social maturity follow children who have experience playing group = 176.675. This suggests that the child's social maturity follow a group that has experience playing better than the child's social maturity with no experience to follow the playing group.